1987
DOI: 10.1002/1097-0142(19901015)60:8+<2075::aid-cncr2820601521>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug resistance in ovarian cancer

Abstract: The development of acquired resistance has limited the effectiveness of chemotherapy in the treatment of ovarian cancer. Experimental model systems were developed to study the mechanisms associated with primary resistance to chemotherapeutic agents and broad cross-resistance (multidrug resistance) which is characteristic of human ovarian cancer. Doxorubicin-resistant cell lines developed in vitro by exposure of a sensitive cell line to increasing concentrations of doxorubicin develop resistance on the basis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(35 citation statements)
references
References 29 publications
0
35
0
Order By: Relevance
“…Earlier studies have found that multiple factors are linked to drug resistance in human ovarian cancer including reduced intracellular drug accumulation, intracellular cisplatin inactivation, and increased DNA repair (4). Reduced cellular drug accumulation is mediated by the copper transporter-1 responsible for the influx of cisplatin (5-9) and MDR1, which encodes an integral membrane protein named P-glycoprotein for the active efflux of platinum drugs.…”
mentioning
confidence: 99%
“…Earlier studies have found that multiple factors are linked to drug resistance in human ovarian cancer including reduced intracellular drug accumulation, intracellular cisplatin inactivation, and increased DNA repair (4). Reduced cellular drug accumulation is mediated by the copper transporter-1 responsible for the influx of cisplatin (5-9) and MDR1, which encodes an integral membrane protein named P-glycoprotein for the active efflux of platinum drugs.…”
mentioning
confidence: 99%
“…[1][2][3] Adriamycin resistance often may also result from overexpression of P-glycoprotein encoded by the MDR-1 gene. 4,5 However, the increased expression of Pglycoprotein and MDR-1 does not always contribute to clinical resistance, at least in lung cancer patients.…”
mentioning
confidence: 99%
“…The amount of MDR1 RNA as well as the amount of Pgp protein present in the target cell lines studied here correlate well with the level of MDR. 25,26 The inhibitory activity of the A2 scFv antibody on MDR cell lines correlates favorably with the level of Pgp overexpression, while the scFv molecule does not exhibit toxic effects on the parental, drug-sensitive cell lines.…”
Section: Discussionmentioning
confidence: 99%